2020
DOI: 10.1093/neuonc/noaa249
|View full text |Cite
|
Sign up to set email alerts
|

Optimal therapeutic targeting by HDAC inhibition in biopsy-derived treatment-naïve diffuse midline glioma models

Abstract: Background Diffuse midline gliomas (DMGs), including diffuse intrinsic pontine gliomas (DIPGs), have a dismal prognosis with less than 2% surviving 5-years post-diagnosis. The majority of DIPGs and all DMGs harbor mutations altering the epigenetic regulatory histone tail (H3 K27M). Investigations addressing DMG epigenetics have identified few promising drugs, including the HDAC inhibitor (HDACi) panobinostat. Here, we use clinically-relevant DMG models to identify and validate other effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 50 publications
(54 reference statements)
1
45
0
1
Order By: Relevance
“… 4 Furthermore, preclinical studies have often found that even epigenetically targeted agents such as HDAC inhibitors are still efficacious against histone wildtype DIPG, supporting some inherent similarities despite molecular distinctions. 51 , 52 While, it would be desirable to identify radiomic features unique to the H3 K27M-mutant subgroup, this was not feasible due to lack of biopsy in the majority of the cases. As biopsy becomes more common, prospective associations between artificial intelligence-based imaging and genomics may provide further insight.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Furthermore, preclinical studies have often found that even epigenetically targeted agents such as HDAC inhibitors are still efficacious against histone wildtype DIPG, supporting some inherent similarities despite molecular distinctions. 51 , 52 While, it would be desirable to identify radiomic features unique to the H3 K27M-mutant subgroup, this was not feasible due to lack of biopsy in the majority of the cases. As biopsy becomes more common, prospective associations between artificial intelligence-based imaging and genomics may provide further insight.…”
Section: Discussionmentioning
confidence: 99%
“…Among the key genes, C1ORF105 was associated with a larger inter-adventitial common carotid artery diameter (ICCAD) (Harrison et al, 2013), and FAM132b can be increased by induction of erythrogenesis (Gurieva et al, 2017), suggesting that they may play an important role in the occurrence and development of cancer. The overexpression of TNNT1 may play a role in the development of diffuse midline gliomas (DMGs) (Vitanza et al, 2020). RspO4 can activate the Wnt/β-catenin signaling pathway and promote the progression of esophageal squamous cell carcinoma (Chai et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, acknowledging the susceptibility of the different glioma molecular subtypes to different treatments to induce ICD. For example, HDAC inhibitors were shown to target K27M HGG ( 260 ), and other tailored therapies are being explored for other subtypes ( 252 ), but the potential combinations of treatments inducing ICD and immunotherapies remain unexplored.…”
Section: Influence Of Genetic Alterations Present In Glioma Subtypes On the Response To Immunotherapiesmentioning
confidence: 99%